Before gender : lost stories from trans history 1850-1950 / Eli Erlick. - Erlick, Eli (Manchester University Press, 2025)
This work rewrites trans history, presenting the stories of thirty extraordinary trans people who lived between 1850 and 1950. Featuring kids, activists, workers and athletes, it reveals the reality of trans lives in an era before the concept of gender became an everyday term.